What is the value of the contract (to be paid at current time $t_0$) that gives one the right (but not obligation) to buy a Vanilla Call option (with certain strike K) at a pre-determined price $p$ at future time $t_e$? The price, $p$ is determined at $t_0$ and paid at $t_e$ if the holder exercises the right to buy the option. Assume the stock is lognormal with constant volatility.


2 Answers 2


The proof is relatively long, so I focus on displaying the reasoning and major steps.

We work on a Black-Scholes model. Without loss of generality, we focus on an option with strike $P$ to buy at $t_e$ a European call option expiring at $T$, written on a stock $S$. Expectations are always taken with respect to the risk-neutral measure $Q$ unless otherwise stated, and we write $E_t(\cdot):=E(\cdot|\mathscr{F}_t)$.

The value $C_t$ of a European call option is equal to: $$C_t=E_t\left(e^{-r(T-t)}\max\{S_T-K\}\right)$$

The value $O_t$ of an option over a European call option is given by: $$\begin{align} O_t &=E_t\left(e^{-r(t_e-t)}\max\{C_{t_e}-P,0\}\right) \\&=e^{-r(t_e-t)}E_t\left( \max\left\{E_{t_e}\left(e^{-r(T-t_e)}\max\{S_T-K,0\}\right)-P,0\right\}\right) \\&=e^{-r(T-t)}E_t \left(1_{S_{t_e}\geq S^\star}\left(E_{t_e}\left(1_{S_T\geq K}\left(S_T-K\right)\right)-\tilde{P}\right)\right) \\&=e^{-r(T-t)}E_t\left(E_{t_e} \left(1_{S_{t_e}\geq S^\star}1_{S_T\geq K}\left(S_T-K\right)-1_{S_{t_e}\geq S^\star}\tilde{P}\right)\right) \\\tag{1}&=e^{-r(T-t)}\left( E_t\left(1_{S_{t_e}\geq S^\star, S_T\geq K}S_T\right) -E_t\left(1_{S_{t_e}\geq S^\star, S_T\geq K}\right)K -E_t\left(1_{S_{t_e}\geq S^\star}\right)\tilde{P} \right) \end{align}$$ where the last inequality stems from the law of iterated expectations, $\tilde{P}:=e^{r(T-t_e)}P$ is the compounded strike, and $S^\star$ is the value of $s$ that solves the following equation: $$\tag{2}c(s,T-t_e)-\tilde{P}=0$$ where $c$ is the undiscounted Black-Scholes price for a European call option: $$c(s,\tau):=se^{r\tau}\Phi\left(\frac{\ln\frac{s}{K}+\left(r+\frac{\sigma^2}{2}\right)\tau}{\sigma\sqrt{\tau}}\right)-K\Phi\left(\frac{\ln\frac{s}{K}+\left(r-\frac{\sigma^2}{2}\right)\tau}{\sigma\sqrt{\tau}}\right)$$

In practice, the quantity $S^\star$ can be computed by solving numerically Equation $(2)$, for example by Newton-Raphson. Now, the third term in Equation $(1)$ is merely the probability of a log-normal variable being above $S^\star$. By analogy with classical Black-Scholes, this is equal to: $$\tag{3.a}E_t\left(1_{S_{t_e}\geq S^\star}\right)=\Phi\left(\frac{\ln\frac{S_t}{S^\star}+\left(r-\frac{\sigma^2}{2}\right)(t_e-t)}{\sigma\sqrt{t_e-t}}\right)$$

To compute the second term in $(1)$, we define $Z$ and $Y$ as two independent normal random variables with zero mean and unit variance in order to represent the Brownian increments from $t$ to $t_e$ and from there to $T$. Note that: $$\begin{align} 1_{\{S_{t_e}\geq S^\star,\ S_T\geq K\}} &=1_{\left\{S_te^{\left(r-\frac{\sigma^2}{2}\right)(t_e-t)+\sigma \sqrt{t_e-t}Z}\geq S^\star,\ S_te^{\left(r-\frac{\sigma^2}{2}\right)(T-t)+\sigma\left(\sqrt{t_e-t}Z+\sqrt{T-t_e}Y\right)}\geq K\right\}} \\\tag{4} &=1_{\left\{Z\leq \frac{\ln\frac{S_t}{S^\star}+\left(r-\frac{\sigma^2}{2}\right)(t_e-t)}{\sigma\sqrt{t_e-t}},\ X\leq \frac{\ln\frac{S_t}{K}+\left(r-\frac{\sigma^2}{2}\right)(T-t)}{\sigma\sqrt{T-t}}\right\}} \end{align}$$ where $X$ is a third standard normal variable with the following correlation with $Z$: $$\rho:=\frac{\text{Cov}(\sqrt{t_e-t}Z+\sqrt{T-t_e}Y,Z)}{\sqrt{V(\sqrt{T-t_e}Z+\sqrt{t_e-t}Y)V(Z)}}=\sqrt{\frac{t_e-t}{T-t}}$$ Hence the second term in Equation $(1)$ is the cumulative bi-variate normal probability over $Z$ and $X$ parameterised by their correlation $\rho$: $$\begin{align} &E_t\left(1_{S_{t_e}\geq S^\star,\ S_T\geq K}\right) \\[6pt]\tag{3.b} &\quad=\Phi_\rho\left(\frac{\ln\frac{S_t}{S^\star}+\left(r-\frac{\sigma^2}{2}\right)(t_e-t)}{\sigma\sqrt{t_e-t}},\frac{\ln\frac{S_t}{K}+\left(r-\frac{\sigma^2}{2}\right)(T-t)}{\sigma\sqrt{T-t}}\right) \end{align}$$

For the first term in Equation $(1)$, we change the measure of the expectation to the stock measure where the numéraire is the stock $S$, which we will write $\mathcal{S}$: $$\begin{align} E_t^\mathcal{Q}\left(1_{S_{t_e}\geq S^\star,\ S_T\geq K}S_T\right) &=E_t^\mathcal{S}\left(e^{r(T-t)}\frac{S_t}{S_T}1_{S_{t_e}\geq S^\star,\ S_T\geq K}S_T\right) \\ &=e^{r(T-t)}S_tE_t^\mathcal{S}\left(1_{S_{t_e}\geq S^\star,\ S_T\geq K}\right) \end{align}$$

The Radon-Nikodym process implied by this change of measure is: $$\begin{align} \left.\frac{d\mathcal{Q}}{d\mathcal{S}}\right|_{\mathscr{F}_t} &=e^{r(T-t)}\frac{S_t}{S_T} \\ &=e^{\frac{\sigma^2}{2}(T-t)-\sigma W^\mathcal{Q}_t} \end{align}$$ The "Novikov process" for this change of measure is therefore $\theta_t:=-\sigma t$. Thus the following process is the Brownian Motion under the stock measure: $$W^\mathcal{S}_t=W^\mathcal{Q}_t-\sigma t$$

This implies that the drift of the stock under this new measure increases by $\sigma^2$. We can leverage Equation $(4)$ but this time on standard normal variables $Z'$, $Y'$ and $X'$ under the stock measure $\mathcal{S}$: $$\begin{align} 1_{\{S_{t_e}\geq S^\star,\ S_T\geq K\}} &=1_{\left\{Z'\leq \frac{\ln\frac{S_t}{S^\star}+\left((r+\sigma^2)-\frac{\sigma^2}{2}\right)(t_e-t)}{\sigma\sqrt{t_e-t}},\ X'\leq \frac{\ln\frac{S_t}{K}+\left((r+\sigma^2)-\frac{\sigma^2}{2}\right)(T-t)}{\sigma\sqrt{T-t}}\right\}} \\ &=1_{\left\{Z'\leq \frac{\ln\frac{S_t}{S^\star}+\left(r+\frac{\sigma^2}{2}\right)(t_e-t)}{\sigma\sqrt{t_e-t}},\ X'\leq \frac{\ln\frac{S_t}{K}+\left(r+\frac{\sigma^2}{2}\right)(T-t)}{\sigma\sqrt{T-t}}\right\}} \end{align}$$ That is: $$\begin{align} &E_t\left(1_{S_{t_e}\geq S^\star,\ S_T\geq K}S_T\right) = \\[6pt] \tag{3.c} & \quad e^{r(T-t)}S_t \Phi_\rho\left(\frac{\ln\frac{S_t}{S^\star}+\left(r+\frac{\sigma^2}{2}\right)(t_e-t)}{\sigma\sqrt{t_e-t}},\frac{\ln\frac{S_t}{K}+\left(r+\frac{\sigma^2}{2}\right)(T-t)}{\sigma\sqrt{T-t}}\right) \end{align}$$ Defining: $$\begin{align} d_1 & := \frac{\ln\frac{S_t}{K}+\left(r+\frac{\sigma^2}{2}\right)(T-t)}{\sigma\sqrt{T-t}} \\ d_1^\star & := \frac{\ln\frac{S_t}{S^\star}+\left(r+\frac{\sigma^2}{2}\right)(t_e-t)}{\sigma\sqrt{t_e-t}} \\[12pt] d_2 & := d_1-\sigma\sqrt{T-t} \\[18pt] d_2^\star & := d_1^\star-\sigma\sqrt{T-t} \end{align}$$ Then combining Equations $(1)$, $(3.a)$, $(3.b)$ and $(3.c)$, we obtain the desired result: $$O_t=S_t\Phi_\rho\left(d_1^\star,d_1\right)-e^{-r(T-t)} K\Phi_\rho\left(d_2^\star,d_2\right)-e^{-r(t_e-t)}P\Phi(d_2^\star) \quad \square$$

As you can see, it is very similar to the Black-Scholes Equation for a call option:

  • The third term of the valuation formula for $O_t$ is equivalent to the second term in the Black-Scholes formula, namely the discounted strike $P$ times the probability that the option on the option will be exercised;
  • The first two terms combined look very close to the Black-Scholes value of a call option: this is to be expected, because the option is written on a call option. However, the probabilities $\Phi_\rho(d_1^\star,d_1)$ and $\Phi_\rho(d_2^\star,d_2)$ account for the value of the stock price at $t_e$ and $T$. This is because when you enter into a vanilla call option, you know the stock price at trade date $t$ but not at expiry $T$. In this case, you will enter the option at a future time $t_e>t$, hence you do not know the value of the underlying neither at inception $t_e$ nor at expiry $T$: this heightened uncertainty is captured by the bi-variate normal distribution.
  • $\begingroup$ Thanks, Daneel for your response. $\endgroup$
    – Toby1729
    Oct 16, 2020 at 8:13
  • $\begingroup$ You're welcome @ahr1729. $\endgroup$ Oct 16, 2020 at 10:16
  • 1
    $\begingroup$ Once you have this formula, to implement it, you will need code to calculate the bivariate normal probabilities $\Phi_{\rho}(\cdot,\cdot)$. Naturally this problem has been studied in the Finance literature and there are various methods available pdfs.semanticscholar.org/8d3e/… $\endgroup$
    – nbbo2
    Oct 19, 2020 at 8:51

I think you are referring to a compound option. It's valuation under Black-Scholes assumptions is given in the link. The option was first derived by Geske (1978), see here for the original paper .

  • $\begingroup$ Thanks, Kermittfrog. $\endgroup$
    – Toby1729
    Oct 16, 2020 at 8:12

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.